2018
DOI: 10.4132/jptm.2018.04.03
|View full text |Cite
|
Sign up to set email alerts
|

Cytologic Diagnosis of Noninvasive Follicular Thyroid Neoplasm with Papillary-like Nuclear Features and Its Impact on the Risk of Malignancy in the Bethesda System for Reporting Thyroid Cytopathology: An Institutional Experience

Abstract: BackgroundThis study was performed to analyze cytologic diagnosis of noninvasive follicular thyroid neoplasm with papillary-like nuclear features (NIFTP) and its impact on the risk of malignancy (ROM) in the Bethesda System for Reporting Thyroid Cytopathology (TBSRTC). MethodsFive thousand five hundred and forty-nine cases of thyroid fine-needle aspiration cytology (FNAC) diagnosed between 2012 and 2014 were included in this study. Diagnostic categories based on TBSRTC were compared with final surgical diagnos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
31
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 22 publications
0
31
0
Order By: Relevance
“…We excluded a further 233 studies and finally selected 38 studies, which included 145,066 thyroid nodules, for meta‐analysis (Fig. ) . Among the included studies, 4 were prospective and 34 were retrospective.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We excluded a further 233 studies and finally selected 38 studies, which included 145,066 thyroid nodules, for meta‐analysis (Fig. ) . Among the included studies, 4 were prospective and 34 were retrospective.…”
Section: Resultsmentioning
confidence: 99%
“…TBSRTC 2017 adopted NIFTP terminology and provided 2 ranges of ROM, one considering NIFTP as malignancy and another not . In the present study, we included 4 studies that applied the post‐NIFTP classification . All patients in these studies received recommendations for surgical intervention before the NIFTP terminology was introduced so the RR was not affected by the updated guidelines.…”
Section: Discussionmentioning
confidence: 99%
“…The reclassification of NIFTP as a non-malignant lesion decreases the ROM in most Bethesda categories; the scale of the impact differs significantly among various institutions (9,11,61,62,63,64,65,66,67,68,69,70). According to the latest large meta-analysis conducted by Vuong et al (14 studies, 14,153 resected nodules), the highest absolute decrease in ROM was observed in SM, FN/SFN and AUS/FLUS categories (15.8%, 10.6% and 9.5%, respectively) (71).…”
Section: Niftp In Fine-needle Aspiration Biopsymentioning
confidence: 99%
“…Clinicians should always be aware of the malignancy rate in various Bethesda categories in their respective hospitals to improve their management decisions. Few studies have shown that NIFTP has affected malignancy risk in each category with the greatest impact being on FN/SFN and nondiagnostic categories . A recent meta‐analysis by Layfield et al has shown that NIFTP remarkably affect risk of malignancy in indeterminate Bethesda categories .…”
Section: Discussionmentioning
confidence: 99%
“…AUS, atypia of undetermined significance; DROM, difference in risk of malignancyFLUS, follicular neoplasm of undetermined significance; FN, follicular neoplasm; NIFTP, noninvasive follicular thyroid neoplasm with papillary-like nuclear features; ROM, risk of malignancy SFN, suspicious of follicular neoplasm. Comparative analysis of ultrasound and cytology findings of NIFTP with other differential diagnosis37,38,42 that NIFTP has affected malignancy risk in each category with the greatest impact being on FN/SFN and nondiagnostic categories 40. A recent meta-analysis by Layfield et al has shown that NIFTP remarkably affect risk of malignancy in indeterminate Bethesda categories.…”
mentioning
confidence: 99%